1994
DOI: 10.1073/pnas.91.8.3388
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional spectral-spatial EPR imaging of free radicals in the heart: a technique for imaging tissue metabolism and oxygenation.

Abstract: It has been hypothesized that free radical metabolism and oxygenation in living organs and tissues such as the heart may vary over the spatially defined tissue structure. In an effort to study these spatially defined differences, we have developed electron paramagnetic resonance imaging instrumentation enabling the performance of threedimensional spectralpatial images of free radicals infufised into the heart and large vessels. Using this instrumentation, high-quality three-dimensional spectralpatial images of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
181
0
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 211 publications
(183 citation statements)
references
References 15 publications
1
181
0
1
Order By: Relevance
“…In addition, we observed that with subsequent i.v. administration of 0.3 ml of 100 mM Na 3 Fe(CN) 6 at a time 50 min post 3-CP infusion, an Ϸ50% return of total EPR signal was seen, confirming that much of the label was reversibly bioreduced within the body.…”
Section: Kinetics Of Nitroxide Radicals In the Whole Body And In Diffmentioning
confidence: 65%
See 1 more Smart Citation
“…In addition, we observed that with subsequent i.v. administration of 0.3 ml of 100 mM Na 3 Fe(CN) 6 at a time 50 min post 3-CP infusion, an Ϸ50% return of total EPR signal was seen, confirming that much of the label was reversibly bioreduced within the body.…”
Section: Kinetics Of Nitroxide Radicals In the Whole Body And In Diffmentioning
confidence: 65%
“…Electron paramagnetic resonance imaging (EPRI) has been widely used to map the distribution and metabolism of paramagnetic species in isolated organs and other ex vivo and in vivo biological systems (1)(2)(3)(4)(5)(6)(7)(8)(9)(10). However, in contrast to proton NMR-based MRI, EPRI only detects the distribution and kinetics of free radicals, and consequently these images may not resemble the anatomic structure of the imaged object.…”
mentioning
confidence: 99%
“…19 Isolated rat hearts were perfused at 37 C in a constant pressure mode with Krebs bicarbonate-buffered perfusate solution. Hearts were infused with 1 mM TEMPO (2,2,5,5-tetramethylpiperidine-Noxyl) for 10 min to reach steady state and EPR acquisitions of 64 projections were performed every 12 min.…”
Section: Imaging Of Myocardial Metabolism Of Nitroxyl Radicals and Oxmentioning
confidence: 99%
“…[9][10][11][12][13][14][15][16][17][18] Over the last decade we have focused on developing instrumentation optimized for measurements of free radicals in isolated beating hearts, and in recent several years we have extended our efforts to develop hardware and software to enable spatial and spectral-spatial imaging of free radicals in the heart. 9,[19][20][21][22][23][24][25] This review provides a summary of the development and application of the imaging techniques with examples including imaging of stable free radical labels, oxygen concentrations and nitric oxide generation in the normal or ischemic heart.…”
Section: Introductionmentioning
confidence: 99%
“…However, due to the nature of field sweep, the imaging time in CW EPRI is relatively long (11). For example, it typically takes several minutes for a conventional EPR imaging system to acquire a 2D image and tens of minutes for a 3D image (12). The long imaging time prevents the use of this technique for many biological applications where the free radicals have a short lifetime or a rapid metabolic clearance (13).…”
Section: Introductionmentioning
confidence: 99%